Structured Laguerre–Gaussian beams for mitigation of spherical aberration in tightly focused regimes. (27th February 2018) - Haddadi, S; Bouzid, O; Fromager, M; Hasnaoui, A; Harfouche, A; Cagniot, E; Forbes, A; Aït-Ameur, K
Abstract: Many laser applications utilise a focused laser beam having a single-lobed intensity profile in the focal plane, ideally with the highest possible on-axis intensity. Conventionally, this is achieved with the lowest-order Laguerre–Gaussian mode (LG00 ), the Gaussian beam, in a tight focusing configuration. However, tight focusing often involves significant spherical aberration due to the high numerical aperture of the systems involved, thus degrading the focal quality. Here, we demonstrate that a high-order radial LG p 0 mode can be tailored to meet and in some instances exceed the performance of the Gaussian. We achieve this by phase rectification of the mode using a simple binary diffractive optic. By way of example, we show that the focusing of a rectified LG50 beam is almost insensitive to a spherical aberration coefficient of over three wavelengths, in contrast with the usual Gaussian beam for which the intensity of the focal spot is reduced by a factor of two. This work paves the way towards enhanced focal spots using structured light.